Short- and long-term effects of physical exercises and verbal stimulation on functional efficiency and use of free time in an older population under institutional care: A randomized controlled trial. - Wiśniowska-Szurlej, Agnieszka; Ćwirlej-Sozańska, Agnieszka; Wołoszyn, Natalia; Sozański, Bernard; Wilmowska-Pietruszyńska, Anna (My University, 2019)
Background: Older people covered by institutional care are mostly physically inactive and uninvolved in interacting with each other and medical staff. Therefore, reducing sedentary behaviour is a new, important, modifiable variable of lifestyle that can improve the health of elderly people. The aim of the project was to assess the degree of improvement in functional performance and the possibility of changing habitual ways of spending free time among elderly people under institutional care, by applying physical training with verbal stimulation. Methods: The study covered older people aged 65-85 years, who are living a sedentary lifestyle in care homes in south-eastern Poland. Those who meet the eligibility criteria and are enrolled in the study was assigned at random to one of four parallel groups: basic exercises (BE), basic exercises combined with verbal stimulation (BE + VS), functional exercise training (FET) and functional exercise training with verbal stimulation (FET + VS). Data were collected at baseline and at 12 and 24 weeks following completion of the program. Results: In the FET + VS group, the greatest positive long-term impact of intervention was demonstrated in terms of functional fitness, gait speed (improved by 0.18m/s), hand grip strength (by over 3.5 kg), and upper limb flexibility (by 10 cm). There was also a significant increase in the level of physical activity spent in free time and an improvement in the quality of life especially expressed in the domain of overall physical functioning. Conclusion: Our study showed that a functional exercise program combined with verbal stimulation is effective in improving physical fitness and raising the level of physical activity spent in free time.
Keywords: Sedentary Behaviour, Aged, Exercise, Motivation